Mevalonate-derived quinonemethide triterpenoid from in vitro roots of Peritassa laevigata and their localization in root tissue by MALDI imaging - Pina, Edieidia S.; Silva, Denise B.; Teixeira, Simone P.; Coppede, Juliana S.; Furlan, Maysa [UNESP]; Franca, Suzelei C.; Lopes, Norberto P.; Pereira, Ana Maria S.; Lopes, Adriana A. (Nature Publishing Group, 2016)
Biosynthetic investigation of quinonemethide triterpenoid 22 beta-hydroxy-maytenin (2) from in vitro root cultures of Peritassa laevigata (Celastraceae) was conducted using C-13-precursor. The mevalonate pathway in P. laevigata is responsible for the synthesis of the quinonemethide triterpenoid scaffold. Moreover, anatomical analysis of P. laevigata roots cultured in vitro and in situ showed the presence of 22 beta-hydroxy-maytenin (2) and maytenin (1) in the tissues from transverse or longitudinal sections with an intense orange color. MALDI-MS imaging confirmed the distribution of (2) and (1) in the more distal portions of the root cap, the outer cell layers, and near the vascular cylinder of P. laevigata in vitro roots suggesting a role in plant defense against infection by microorganisms as well as in the root exudation processes.